ESTIMASI POTENSI KERUGIAN EKONOMI DAN BIAYA PENANGGULANGAN AKIBAT ANEMIA DI INDONESIA - Mangalik, Gelora; Martianto, Drajat; Sukandar, Dadang (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
The aim of this study was to estimate the economic loss and cost of intervention due to iron deficiency anemia (IDA) in Indonesia. The data in this research were secondary data from several related institution. Potential economic losses due to IDA can be estimated by calculating the economic value of cognitive impairment, reduced work productivity, and increased maintenance costs due to low birth weight. The economic value of cognitive impairment estimated by multiplying the wages, prevalence and population. The economic value of decreased productivity of labour was estimated by multiplying the wages of non-agricultural, agricultural wages, prevalence, population and labor force participation rate (LFPR). The result of this research are the total amount of potential national loss due to IDA approximately Rp 62.02 trillion per year (US5.08 billion) representing 0.711% of the country’s GDP and the cost for intervention approximately Rp 1.95 billion per year (US150 milion). The cost of intervention is less than the economic loss.Keywords: cost of intervention, economic loss, iron deficiency anemia